A STUDY ON SERUM BIOCHEMICAL VALUES ON NORMAL ARABIAN CAMELS IN IRAQ - K. AL-DELAIMI, A.; H. ALI , A.; S. JERMUKLY , M. (The Iraqi Journal of Veterinary Medicine, 1990)
Biochemical values for fifty clinically healthy arabian camels of both sex were determined for the normal activities of serum glutamic oxal transaminase, serum urea, Alkaline glutamic pyruvic tranaminase, blood phsphatase, cholesterol, bilirubin, glucose, calcium, Magnaesium, phosphorus, creatinine, sodium, potassium, total protein and albumin. Comparison of the above values between males and femles revealed only a significant increase (P <0.05) in the values of total protein and magnessium of the females than that in males whereas the creatinine value decreased significantly in females (P> 0.05) than in males. However, defferences in the mean value of the above remaining values among the two groups of males and females were not statistically significant.